2016
DOI: 10.1177/1359105315604378
|View full text |Cite
|
Sign up to set email alerts
|

Emotional management and quality of life in mother living versus multi-organ donor renal transplant recipients

Abstract: The aim of this study was to evaluate psychological differences and quality of life between kidney recipients from living (mother) and multi-organ donor. Overall, 40 patients who had undergone both living (mother) and multi-organ kidney transplantation 3-6 months before were asked to complete four self-report instruments: Toronto Alexithymia Scale, Short Form Health Survey, Regulatory Emotional Self-efficacy, and Attachment Style Questionnaire. A greater difficulty in emotional, social, and mental health funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…It has been shown that some psychological characteristics such as attachment style and alexithymia may affect compliance, quality of life, and renal function in patients undergoing kidney transplant. A greater difficulty in emotional, social, and mental health functioning was found in recipients receiving kidney from mother living donor indicating that the donor characteristics (parent derived or multi-organ-derived) may affect psychological status and quality of life (Calia et al, 2015a, 2015b, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that some psychological characteristics such as attachment style and alexithymia may affect compliance, quality of life, and renal function in patients undergoing kidney transplant. A greater difficulty in emotional, social, and mental health functioning was found in recipients receiving kidney from mother living donor indicating that the donor characteristics (parent derived or multi-organ-derived) may affect psychological status and quality of life (Calia et al, 2015a, 2015b, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplantation is a replacement procedure for chronic kidney disease that is intended to improve the patient’s quality of life. However, the experience may be a strongly emotional one, accompanied by difficulty in accepting the new organ, lifestyle changes, the side-effects associated with the procedure, anxiety, depression, the redefinition of one’s body, and a change in social and family roles [ 1 , 2 , 3 , 4 , 5 ]. Hence, the associated stress may result in an adverse post-operative course, particularly in terms of compliance to the follow-up process, medical prescriptions, and the consequential risk of rejection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent review of literature concluded that relevant psychological predictors of weight loss after bariatric surgery have not been well identified (Wimmelmann et al, 2014), despite they could explain the wide difference in surgical outcome. Alexithymia, beside other more common psychological characteristics such as anxiety and depression, has been found able to affect adherence to the medical and dietary recommendations in other clinical conditions (Aceto et al, 2016; Calia et al, 2011a, 2011b, 2011c, 2015a, 2015b, 2015c; Lai et al, 2016). Therefore, the role of alexithymia could be crucial in affecting weight loss in bariatric patients.…”
Section: Introductionmentioning
confidence: 99%